2022
DOI: 10.3389/fnhum.2022.935213
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning analysis reveals abnormal functional network hubs in the primary angle-closure glaucoma patients

Abstract: BackgroundPrimary angle-closure glaucoma (PACG) is a serious and irreversible blinding eye disease. Growing studies demonstrated that PACG patients were accompanied by vision and vision-related brain region changes. However, whether the whole-brain functional network hub changes occur in PACG patients remains unknown.PurposeThe purpose of the study was to investigate the brain function network hub changes in PACG patients using the voxel-wise degree centrality (DC) method.Materials and methodsThirty-one PACG p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…In our study, the sFNC analysis identified abnormal interactions among the Sensorimotor network (SMN), attention network (AN), and visual network (VN) in PACG patients, partially corroborating previous neuroimaging findings in this patient group 32 , 33 . The crucial pathological feature in PACG patients is the apoptosis of retinal ganglion cells, which unquestionably results in alterations to the visual network.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the sFNC analysis identified abnormal interactions among the Sensorimotor network (SMN), attention network (AN), and visual network (VN) in PACG patients, partially corroborating previous neuroimaging findings in this patient group 32 , 33 . The crucial pathological feature in PACG patients is the apoptosis of retinal ganglion cells, which unquestionably results in alterations to the visual network.…”
Section: Discussionsupporting
confidence: 90%
“…Cai et al 12 found that the degree centrality (DC) values of bilateral visual cortex and left anterior central gyrus in PACG patients after surgery were significantly higher than those before surgery. Chen et al 13 found that PACG patients exhibited extensive dysfunction in the visual network, auditory network, default mode network, and cerebellar network, which may provide new clues to the neural mechanisms of optic atrophy in PACG patients. The above studies suggest that patients with PACG exhibit specific functional irregularities within interregional and global brain networks.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the sFNC analysis identi ed abnormal interactions among the Sensorimotor Network (SMN), Attention Network (AN), and Visual Network (VN) in PACG patients, partially corroborating previous neuroimaging ndings in this patient group 32,33 . The important caseological feature of PACG patients is apoptosis of retinal ganglion cells, which undoubtedly leads to changes in the visual network.…”
Section: Discussionsupporting
confidence: 90%
“…Cheng et al used voxel-wise degree centrality (DC) to study alterations in brain functional network hubs in PACG individuals. Results showed a notable decline in DC values within the DMN among PACG patients, signaling reduced functional connectivity in this network [27]. Similarly, both Yan et al and Yong et al observed disrupted FC between brain hemispheres during resting-state in PACG patients, with impairment observed within the DMN, which is a high-level visual area [28,29].…”
Section: Introductionmentioning
confidence: 73%
“…used voxel-wise degree centrality (DC) to study alterations in brain functional network hubs in PACG individuals. Results showed a notable decline in DC values within the DMN among PACG patients, signaling reduced functional connectivity in this network [27]. Similarly, both Yan et al .…”
Section: Introductionmentioning
confidence: 84%